PENGARUH PEMBERIAN REINFORCEMENT DAN SELF-EFFICACY SISWA DALAM MENINGKATKAN PRESTASI BELAJAR SISWA - Roberto Yunus Liufeto; Hendrik A. E. Lao; Umar Ali (Jurnal Dedikasi Pendidikan, 2023)
The objectives of this study are 1). To determine how the effect of giving reinforcement in improving student learning achievement, 2). To determine how the effect of providing student self-efficacy in improving student learning achievement, 3). To find out how the effect of giving reinforcement and student self-efficacy in improving student learning achievement. The data collection method used is quantitative research method with survey research type. The population in this study were 40 students of class X SMTK Mardhi Wacana Alor Fanating and the sample used in this study were all grade X students of SMTK Mardhi Wacana Alor Fanating. The results of this study are (1). The results of the analysis of this study show that the acquisition of the R value is 0.096 and the R Squared value is in the range of 0.009. This shows that the reinforcement variable (X1) has a very low influence on the student learning achievement variable (Y). meaning that if the reinforcement value decreases, it will be followed by a decrease in student learning achievement. The R Squared value which is in the range of 0.009 is equivalent to 0.9%. This means that there is a very low influence between reinforcement (X1) on student learning achievement (Y) of 0.9%. (2). The result of this research analysis shows that the acquisition of R value is 0.413 and R Squared value is in the range of 0.170. This shows that the self-efficacy variable (X2) has a negative influence on the student learning achievement variable (Y). meaning that if the self-efficacy value increases, it will be followed by an increase in student learning achievement. The R Squared value which is in the range of 0.170 is equivalent to 17.0%. This means that there is an influence between self-efficacy (X2) on student learning achievement (Y) of 17.0%. (3). The results of the analysis of this study indicate that the reinforcement variable X1 and self-efficacy X2 have a negative influence on the student learning achievement variable (Y). meaning that if the value of reinforcement and self-efficacy increases, it will be followed by an increase in student learning achievement. The R Squared value which is in the range of 0.175 is equivalent to 17.5%. So that the higher the provision of reinforcement and student self-efficacy given, the more student learning achievement will increase.